Classification, Electrophysiological Features and Therapy of Atrioventricular Nodal Reentrant Tachycardia - Katritsis, Demosthenes G (Arrhythm Electrophysiol Rev, 2016)
Atrioventricular nodal reentrant tachycardia (AVNRT) should be classified as typical or atypical. The term ‘fast-slow AVNRT’ is rather misleading. Retrograde atrial activation during tachycardia should not be relied upon as a diagnostic criterion. Both typical and atypical atrioventricular nodal reentrant tachycardia are compatible with varying retrograde atrial activation patterns. Attempts at establishing the presence of a ‘lower common pathway’ are probably of no practical significance. When the diagnosis of AVNRT is established, ablation should be only directed towards the anatomic position of the slow pathway. If right septal attempts are unsuccessful, the left septal side should be tried. Ablation targeting earliest atrial activation sites during typical atrioventricular nodal reentrant tachycardia or the fast pathway in general for any kind of typical or atypical atrioventricular nodal reentrant tachycardia, are not justified. In this review we discuss current concepts about the tachycardia circuit, electrophysiologic diagnosis, and ablation of this arrhythmia.